Unpacking the complexity of improved nutrition in Ghana: A consultative process with national stakeholders: A meeting report - University of Ghana; International Food Policy Research Institute (International Food Policy Research Institute, 2020)
Over the past decade, Ghana has achieved significant reductions in hunger and improvement in nutrition of women and children. Undernourishment rate (Food Balance Sheet indicator) has declined and remained below 5% over the past decade. 1 Young child growth has improved as indicated by reduced stunting (low height-for-age), from 28% in 2008 to 19% in 2014; underweight, from 14% in 2008 to 11% in 2014; and wasting- from 8.5% in 2008 to 5% in 2014.2 However, in the context of increasing urbanization and income growth, challenges of urban food and nutrition insecurity and overnutrition have begun to arise. Understanding the drivers of these positive changes will provide useful lessons for future actions for food and nutrition security. While consideration of emergent problems related to urbanization and overnutrition is also necessary. This requires broad consideration of the actions and occurrences that may have contributed in the past, and how Ghana’s changing food system can be leveraged for future progress. To achieve these objectives, two new research initiatives have commenced in Ghana. These are ‘Stories of Change in Nutrition in Ghana’, and ‘Leveraging Food Systems for Improved Nutrition in Ghana’. Both have been initiated by the International Food Policy Research Institute (IFPRI). This report provides a summary of a consultative stakeholder meeting held jointly by the two initiatives on July 3, 2018 in Accra, to engage key stakeholders just as the two initiatives are commencing activities in Ghana. The purpose of the meeting was to introduce participants to the research plans and activities and to present preliminary findings. The meeting also was an opportunity to seek stakeholder input on: a) the actors, actions, and policy processes that have led to improvements in key nutrition problems in the past ; and b) the opportunities for leveraging a changing food system for continued progress on nutrition. Finally, the meeting also sought to learn from stakeholders what were feasible approaches and pathways for engagement and participation. Proceedings of the meeting are presented in this report.